A systematic analysis of the global, regional, and national burden of fungal skin diseases from 1990 to 2021 - Wang, Hongping; Sun, Fengjun; Wang, Changquan; Ye, Jin; Xia, Peiyuan; Wang, Wanneng; Wu, Yaguang (Frontiers in Epidemiology, 2024)
Purpose We aimed to assess the burden of Fungal Skin Diseases (FSD) in 2021 and explore the changing trends from 1990 to 2021 across different age groups and time periods. Methods This study extracted three key indicators of the burden of FSD from the Global Burden of Disease (GBD) 2021 study: prevalence, incidence, and disability-adjusted life years (DALYs). The results were presented using point estimates and Uncertainty Intervals (UIs), and secondary analysis was conducted on these data to assess the changing trends in the burden of FSD using percentage change. Results In 2021, the global cases of prevalence, incidence, and DALYs of FSD were reported at 616.5 million, 1,729.2 million, and 3,429.5 thousand, respectively, an increase of approximately 68% since 1990. The age-standardized rates per 100,000 population for prevalence, incidence, and DALYs were 7,789.6, 21,668.4, and 43.4, respectively. These rates represent percentage increases of 6.21%, 3.74%, and 6.56% since 1990. In terms of age distribution, the ages for FSD-related prevalence, incidence, and DALYs peak cases globally were in the 5–9 age group, with distinct age groups observed in low and low-middle, middle, high-middle and high SDI regions at 5–9 years, 45–49 years, and 70–74 years, respectively. Conclusion Over the past 32 years, there has been a significant increase in the global burden of FSD. With improvements in the Socio-Demographic Index (SDI), the age groups for FSD-related peak cases are gradually shifting towards older age groups. This indicates the need to allocate healthcare resources rationally to address the challenges arising from the significant differences in geographic distribution, gender, and among different populations.